Timing matters! Academic assessment changes throughout the day - Carmelo M. Vicario; Michael A. Nitsche; Chiara Lucifora; Pietro Perconti; Mohammad A. Salehinejad; Francesco Tomaiuolo; Simona Massimino; Alessio Avenanti; Massimo Mucciardi (Frontiers in Psychology, 2025)
The influence of timing on decision-making processes has garnered significant attention across various domains, yet its impact on academic assessment remains under investigated. While previous research has suggested time-of-day effects on judicial decisions, methodological limitations have restricted the generalizability of these findings. Here, we present a comprehensive analysis of 104.552 oral exams conducted at an Italian university, revealing a robust relationship between exam timing and academic outcomes. Our results demonstrate a Gaussian distribution of passing rates throughout the day, with a significant peak at midday. This pattern persists after controlling for exam difficulty and other potential confounding factors, suggesting an intrinsic time-dependent bias in the evaluation process. Our findings not only corroborate previous research on the influence of timing on decision-making but also extend it to the realm of academic assessment. These results have profound implications for educational policy and practice, highlighting the need for strategic exam scheduling to optimize student performance and ensure equitable evaluation.